2012
DOI: 10.5604/15093492.1005085
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Validity, Reliability, Responsiveness and Bias of Three Commonly Used Patient-Reported Outcome Measures in Carpal Tunnel Syndrome

Abstract: 1. This study ha show n that the BQ, DASH and M(2)DASH questionnaires are valid and reliable outcome measures for CTS. 2. In terms of responsiveness, the DASH and M(2)DASH questionnaires are not as responsive as the BQ scores over the initial post-operative recovery period. 3. We would therefore recommend that the Boston Questionnaire be used to assess early post-operative patient related outcome measures for Carpal Tunnel Syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…The exclusion criteria for participation were CTS patients, diabetic patients, history of wrist surgery or wrist fracture. All participants were free of signs and symptoms of CTS, as indicated by screening tests including the Boston Carpal Tunnel Questionnaire, Phalen Test, and CTS Tinel Test [ 14 16 ]. The physical anthropology characteristic of participants such as height, weight and wrist circumference were presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria for participation were CTS patients, diabetic patients, history of wrist surgery or wrist fracture. All participants were free of signs and symptoms of CTS, as indicated by screening tests including the Boston Carpal Tunnel Questionnaire, Phalen Test, and CTS Tinel Test [ 14 16 ]. The physical anthropology characteristic of participants such as height, weight and wrist circumference were presented in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…This instrument has been shown to be reliable, valid, and responsive in peripheral nerve injury assessment. 22,23 Data/Statistical Analysis All results are reported as mean 6 standard deviation. Perprotocol analysis was done.…”
Section: Disabilitymentioning
confidence: 99%
“…Electrodiagnostic findings have also been compared with scores on the DASH. Bakhsh et al, 22 in a 2012 study, found no correlation between DASH scores and individual electrodiagnostic parameters. The authors did not provide any electromyographic data, and as such the correlation of DASH score with nerve conduction parameters is of limited value relative to the categorization of CTS severity.…”
Section: Discussionmentioning
confidence: 94%